AKP's neoliberal populism and contradictions of new social policies in Turkey. Issue 3 (26th May 2020) - Özdemir, Yonca
ABSTRACT: The AKP came to power in Turkey in 2002 after a devastating economic crisis and has since become a hegemonic party. Despite its neoliberal policies, its votes mostly come from the poorer echelons of the society. This article analyses the AKP as a prime example of 'neoliberal populism' and argues that the AKP's social policies are the material sources of its neoliberal populism. There are, however, important contradictions in AKP's social policies. First, they have mostly beneﬁted informal sector workers, but have decreased the beneﬁts of formal employees. Second, some of the social policies are programmatic and universal, but others are particularistic and clientelistic. Third, although social programmes and spending increased, the labour policies of AKP have decreased the power and conditions of labour. These social policy contradictions help AKP target the poor unorganized sections of the society, gain and maintain popularity among them and weaken opposition to its neoliberalism and authoritarianism.